A Facile Strategy to Fabricate Thermoresponsive Polymer Functionalized CdTe/ZnS Quantum Dots: Assemblies and Optical Properties. Issue 1 (27th November 2013) - Liu, Bingxin; Tong, Cuiyan; Feng, Lijuan; Wang, Chunyu; He, Yao; Lü, Changli
<x xml:space="preserve">Abstract</x> Novel thermoresponsive CdTe/ZnS quantum dots (QDs) decorated with a copolymer ligand (CPL) containing 8‐hydroxyquinoline and NIPAM units are prepared through coordinate bonding in aqueous solution. The dependence of the morphology and optical properties of the QDs/CPL assemblies formed via coordinate bonding on the experimental conditions is studied. The coordinate induced self‐assemblies are observed by controlling the molar ratio of QDs and CPL. The self‐organized structure of QDs/CPL proceeds through a first step of QDs‐chains, followed by a necklace‐like single annular chain, and subsequently increases its annular chain structure, forming a network. The CPL functionalized QDs can emit multiple colors from the cooperating interaction between the inherent emission (606 nm) of the QDs and the surface‐coordinated emission (517 nm) of the CPL complex formed on the QD surface. For QDs‐CPL systems, both Förster resonance energy transfer (FRET) and a high rate of photoinduced electron transfer (PET) are simultaneous, the latter mainly contributing to PL quenching. The thermoresponsive QDs/CPL assemblies also exhibit dual reversible PL properties between the inherent emission of QDs and surface‐coordinated emission. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>